Makna Upacara Balian dalam Ritual Pengobatan Tradisional Suku Paser Kabupaten Paser - Cucu Widaty; Yuli Apriati; Aldian Hudaya; Siska Kusuma (Jurnal Sosiologi Pendidikan Humanis, 2021)
This study describes the balian ceremony in the form of a ritual that is carried out as a traditional treatment in the Paser tribe, Paser district, East Kalimantan. This is motivated by the belief of the Paser people who still maintain healing rituals with the balian ceremony because of hereditary and entrenched beliefs, considerations of alternative medicine, perceptions and views of life. This study aims to uncover 3 important focuses, namely: the form of the balian ceremony procession, the meaning of the balian ceremony for the Paser tribal community, and the function of the balian ceremony. The research method used in this study is qualitative with an ethnographic approach. This study uses data collection techniques in the form of observation, in-depth interviews, and documentation with primary data sources and secondary data sources. The results showed that the form of the balian ceremony procession consists of three stages, the first is the preparation stage, namely the organizer prepares the equipment and coordinates with the parties involved in the balian ceremony. Second, the core activity stage is a mulung dancing along with reciting healing spells. Third, the closing stage is mulung awareness, wiping water, and returning ceremonial equipment. The meaning of the Balian ceremony is the struggle for life, harmony, welfare, safety, good morals, and opening of sustenance, the meaning of asking for protection, remembering God, and remembering the nature of life. The function of the balian ceremony is an effort to heal patients, as a medium of public entertainment, as a medium for connecting the Paser tribal community to the spirits of their ancestors. Penelitian ini mendeskripsikan upacara balian berupa ritual yang dilaksanakan sebagai pengobatan tradisional pada suku Paser kabupaten Paser Kalimantan Timur. Hal ini dilatarbelakangi kepercayaan masyarakat Paser yang tetap mempertahankan ritual penyembuhan dengan upacara balian karena kepercayaan turun-temurun dan membudaya, pertimbangan pengobatan alternatif, persepsi dan pandangan hidup. Penelitian ini bertujuan untuk menguak menguak 3 fokus penting yakni: bentuk prosesi upacara balian, makna upacara balian bagi masyarakat suku Paser, dan fungsi upacara balian. Metode penelitian yang digunakan dalam penelitian ini adalah kualitatif dengan pendekatan etnografi. Penelitian ini menggunakan teknik pengumpulan data berupa observasi, wawancara mendalam, dan dokumentasi dengan sumber data primer dan sumber data sekunder. Hasil penelitian diketahui bahwa bentuk prosesi upacara balian terdiri dari tiga tahap, Pertama tahap persiapan yaitu penyelenggara mempersiapkan perlengkapan dan berkoordinasi dengan pihak yang terlibat pada upacara balian. Kedua, tahap kegiatan inti yaitu seorang mulung menari bersamaan dengan pembacaan mantra penyembuhan. Ketiga, tahap penutup yaitu penyadaran mulung, pengusapan air ,dan pengembalian peralatan upacara. Makna dari dilaksanakannya upacara balian adalah perjuangan hidup, keharmonisan, kesejahteraan, , keselamatan, moral baik,dan pembuka rezeki, makna memohon perlindungan, mengingat tuhan, dan mengingat alam kehidupan. Fungsi upacara balian adalah upaya penyembuhan pasien, sebagai media hiburan masyarakat, sebagai media penghubung masyarakat suku Paser terhadap roh leluhurnya.